Comparative Genomic Analysis of Lactococcus garvieae Strains Isolated from Different Sources Reveals Candidate Virulence Genes. (9th May 2012) - Miyauchi, Eiji; Toh, Hidehiro; Nakano, Akiyo; Tanabe, Soichi; Morita, Hidetoshi
Abstract : Lactococcus garvieae is a major pathogen for fish. Two complete (ATCC 49156 and Lg2) and three draft (UNIUD074, 8831, and 21881) genome sequences of L. garvieae have recently been released. We here present the results of a comparative genomic analysis of these fish and human isolates of L. garvieae . The pangenome comprised 1, 542 core and 1, 378 dispensable genes. The sequenced L. garvieae strains shared most of the possible virulence genes, but the capsule gene cluster was found only in fish-pathogenic strain Lg2. The absence of the capsule gene cluster in other nonpathogenic strains isolated from mastitis and vegetable was also confirmed by PCR. The fish and human isolates of L. garvieae contained the specific two and four adhesin genes, respectively, indicating that these adhesion proteins may be involved in the host specificity differences of L. garvieae . The discoveries revealed by the pangenomic analysis may provide significant insights into the biology of L. garvieae .